PENGARUH KEPEMIMPINAN VISIONER TERHADAP MUTU LAYANAN SEKOLAH DI SMPN SATU ATAP 01 NANGGUNG BOGOR - Nugraha, Acep; Rahmawati, Ima; Halimah, Siti (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2022)
Quality Of School Services basically an quality with regard to activities serve the needs of students, so that all feel satisfied with the services provided by the school. study aims to 1) determine whether there is the effect of visionary leadership on quality of school services,. This research was conducted at SMPN One Roof 01 Nanggun, Bogor Regency. Methods of data collection using a questionnaire and interviews. The method of collecting questionnaire data was carried out on respondents by taking the sample using the Non Probability Sampling technique, using the saturated sampling method. The data analysis technique used simple linear regression analysis. The results showed that there was a positive influence between Visionary leadership on Quality Of School Services. So it can be concluded that H0 is rejected and H1 is accepted